Citizen participation in multiscale planning: the case of “26 Local Strategies: A Metropolitan Plan” in the Rosario Metropolitan Area, Argentina (2016–2020) - Galimberti, Cecilia Inés (2022)
One of the greatest challenges of contemporary planning lies in expanding the strategies and mechanisms of citizen participation in the different scales involved in urban-territorial transformation. In this context, this fieldnote explores the programme “26 Local Strategies: A Metropolitan Plan”, developed in the Rosario Metropolitan Area (AMR), Argentina, by the Rosario Metropolitan Coordination Entity (ECOMR), between 2016 and 2020. This case study is a significant contribution on the topic of participatory strategies in multilevel planning. During the formulation of 24 local urban plans and an interjurisdictional plan, which together constitute the metropolitan plan, it was possible to implement a multiscalar approach, with the wide participation of various social groups, entities, organisations and citizens involved, through which the urban and territorial policies of the AMR were co-designed for the following 10 years.